Antioxidant Potential of Xanthohumol in Disease Prevention: Evidence from Human and Animal Studies - Jakub Piekara; Dorota Piasecka-Kwiatkowska (Antioxidants)
Xanthohumol (XN) is a phenolic compound found in the largest amount in the flowers of the hop plant, but also in the leaves and possibly in the stalks, which is successfully added to dietary supplements and cosmetics. XN is known as a potent antioxidant compound, which, according to current research, has the potential to prevent and inhibit the development of diseases, i.e., cancer and neurodegenerative diseases. The review aims to examine the antioxidant role of XN in disease prevention, with an emphasis on the benefits and risks associated with its supplementation. The regulation by XN of the Nrf2/NF-kB/mTOR/AKT (Nuclear factor erythroid 2-related factor 2/Nuclear factor kappa-light-chain-enhancer of activated B cells/Mammalian target of rapamycin/Protein Kinase B) pathways induce a strong antioxidant and anti-inflammatory effect, among others the acceleration of autophagy through increased synthesis of Bcl-2 (B-cell lymphoma 2) proteins, inhibition of the synthesis of VEGF (Vascular-endothelial growth factor) responsible for angiogenesis and phosphorylation of HKII (Hexokinase II). It is the key function of XN to ameliorate inflammation and to promote the healing process in organs. However, existing data also indicate that XN may have adverse effects in certain diseases, such as advanced prostate cancer, where it activates the AMPK (activated protein kinase) pathway responsible for restoring cellular energy balance. This potential risk may explain why XN has not been classified as a therapeutic drug so far and proves that further research is needed to determine the effectiveness of XN against selected disease entities at a given stage of the disease.